Vollendet - Unvollendet : 13 Werke aus der Sammlung des Kunsthauses - Hnikova, Dagmar; Baumann, Felix (Zürich : Kunsthaus Zürich, 1977)
Daumier, Honoré ; Leibl, Wilhelm ; Manet, Edouard ; Stauffer-Bern, Karl ; Cézanne, Paul ; Modigliani, Amedeo ; Rouault, Georges ; Kokoschka, Oskar ; de La Fresnaye, Roger ; Hodler, Ferdinand ; Despiau, Charles ; Giacometti, Alberto ; Picasso, Pablo
Vollendet - Unvollendet : 13 Werke aus der Sammlung des Kunsthauses, Kunsthaus Zürich, 21. Mai bis 28. Oktober 1977
Duits
kunstcatalogus